Molecular epidemiology of group B streptococcal - Florindo, C. (2012)
Streptococcus agalactiae is a major pathogen of neonates and immunocompromised adults. Prior studies have demonstrated that, beyond the neonatal period, S. agalactiae rarely causes invasive infections in children. However, during 2004–2005, S. agalactiae was the causative agent of 60 meningitis episodes in children aged 3 months to 12 years from Angola. To identify and study the specific causative genetic lineages of S. agalactiae childhood meningitis, which lack characterization to date, we conducted an extensive molecular analysis of the recovered isolates (n521). This constitutes what we believe to be the first molecular study of the population structure of invasive S. agalactiae isolates from Africa. A low genetic diversity was observed among the isolates, where the majority belonged to clonal complex (CC) 17 presenting the capsular subtype III-2 (86% of cases) and marked by the intron group II GBSi1, which has previously been observed to be associated with neonatal hosts. The predominance of single-locus variants of sequence type (ST) 17 suggested the local diversification of this hypervirulent clone, which displayed novel alleles of the fbsB and sip virulence genes. The absence of the scpB–lmb region in two S. agalactiae isolates with the Ia/ST23 genotype is more typical of cattle than human isolates. Globally, these data provide novel information about the enhanced invasiveness of the CC17 genetic lineage in older children and suggest the local diversification of this clone, which may be related to the future emergence of a novel epidemic clone in Angola.